The Role of Circular Economy in Green Entrepreneurship: Sustainable Business Models - Rahim Munir; Rafika Fausiah (Journal of Indonesian Scholars for Social Research, 2025)
The circular economy has emerged as a transformative framework for achieving sustainability in entrepreneurship by minimizing waste, optimizing resource use, and promoting regenerative business practices. Unlike the traditional linear economy that follows a "take, make, dispose" model, the circular economy encourages businesses to adopt reduce, reuse, recycle, and regenerate principles. This study explores the role of circular economy practices in green entrepreneurship, focusing on how sustainable business models integrate environmental responsibility with economic viability. Using a qualitative research approach, this study examines case studies of green entrepreneurs who have successfully implemented circular business models across various industries, including renewable energy, eco-friendly manufacturing, waste management, and sustainable agriculture. The findings indicate that businesses adopting circular economy principles experience benefits such as cost savings, enhanced brand reputation, regulatory compliance, and long-term profitability. However, challenges remain, particularly in terms of scalability, consumer awareness, and access to financing. The study underscores the importance of policy support, technological innovation, and industry collaboration in accelerating the transition toward circular entrepreneurship. By integrating circular economy strategies into their business operations, green entrepreneurs can drive sustainable economic growth, reduce environmental impact, and contribute to global climate resilience. The findings provide valuable insights for business leaders, policymakers, and sustainability advocates on fostering a thriving circular economy ecosystem.